Event marketing and Its impact on tourism industry: in the perspective of Asiatic Experiential Marketing LTD. - Hossain, S. M. Khalid (BRAC Univeristy, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.